Faktor Yang Berhubungan Dengan Kinerja Petugas KIA di Puskesmas Tuppu Kecematan Lembang Kabupaten Pinrang - Rosdiana; Muhammad Alwy Arifin; Suci Rahmadani (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
One of the tasks of implementing the MCH program is antenatal care which aims to monitor the progress of pregnancy, ensure the health of the mother and baby's growth and development, improve and maintain the physical, mental and social health of the mother and baby, recognize early on any abnormalities or complications that may occur during pregnancy. This can be known to be known by MCH officers if carrying out antenatal services according to standards. To find out the factors related to the performance of KIA officers at the Tuppu Health Center, Lembang District, Pinrang Regency. This type of research is analytic observational with a cross sectional study design carried out in the working area of ​​the Tuppu Public Health Center, Lembang District, Pinrang Regency on 27 April – 21 May 2022. The population in this study were all midwives in the Tuppu Health Center Work Area as many as 52 people and a sample of 52 midwives. The sampling technique uses total sampling. Data were analyzed univariately and bivariately using chi square test and fisher's exact. Respondents with less ability were 40 people (76.9%) and 12 people with good ability (23.1%). Respondents who have a positive attitude are 23 people (44.2%) and respondents who are not good are 10 people (19.2%). Fisher's exact results showed that ability (p=0,500), motivation (p=0,480) and the results of the chi-square test showed that attitudes (p=0,111) were not related to the performance factor of the Tuppu Public Health Center, Lembang District, Pinrang Regency.. There is no relationship between ability, attitude and motivation with the performance of officers in maternal and child health services at the Tuppu Public Health Center, Lembang District, Pinrang Regency. For further researchers, they can examine different variables related to the performance of midwives, especially in maternal and child health services.